Has anyone seen a young NEET? Reflections on a case of “symbolic efficacy” and domination - Médor, Ducange (2024)
It’s usual that the media construct false social problems that are later converted into public problems by scholars and, finally, become the object of public policy. Discursive fictions are transformed, presented and imposed as bare reality. The so-called “problem of young people who neither work nor study (NEET)” is a paradigmatic case of this situation, as we try to argue in these reflections. We formulate two hypotheses that are supported by the works of Bourdieu (2001) on symbolic effective- ness and Gusfield (2014) on the ideological construction of public problems: the issue in question is an artifice of language based on the power of its bearers to create realities by naming them; and it reflects the “moral panic” that a certain category of young people, seen as morally and intellectually weak children, causes on some groups of adults; which leads to naming them (NEET) and building control and domination devices in line with the prejudices and anxieties of adults. In this process, young people´s real interests, fears, concerns and desires are what matter the least.